Communities on the Move: Pedestrian-Oriented Zoning as a Facilitator of Adult Active Travel to Work in the United States - Chriqui, Jamie F.; Leider, Julien; Thrun, Emily; Nicholson, Lisa M.; Slater, Sandy (Frontiers in Public Health, 2016)
Background: Communities across the United States have been reforming their zoning codes to create pedestrian-friendly neighborhoods with increased street connectivity, mixed-use and higher density, open space, transportation infrastructure, and a traditional neighborhood structure. Zoning code reforms include new urbanist zoning such as the SmartCode, form-based codes, transects, transportation and pedestrian-oriented developments, and traditional neighborhood developments. Purpose: To examine the relationship of zoning code reforms and more active living-oriented zoning provisions with adult active travel to work via walking, biking, or by using public transit. Methods: Zoning codes effective as of 2010 were compiled for 3,914 municipal-level jurisdictions located in 471 counties and 2 consolidated cities in 48 states and the District of Columbia, and that collectively covered 72.9% of the U.S. population. Zoning codes were evaluated for the presence of code reform zoning and nine pedestrian-oriented zoning provisions (1=yes): sidewalks, crosswalks, bike-pedestrian connectivity, street connectivity, bike lanes, bike parking, bike-pedestrian trails/paths, mixed use development, and other walkability/pedestrian-orientation. A zoning scale reflected the number of provisions addressed (out of 10). Five continuous outcome measures were constructed using 2010-2014 American Community Survey municipal-level 5-year estimates to assess the percentage of workers: walking, biking, walking or biking, or taking public transit to work OR engaged in any active travel to work. Regression models controlled for municipal-level socioeconomic characteristics and a GIS-constructed walkability scale and were clustered on county with robust standard errors. Results: Adjusted models indicated that several pedestrian-oriented zoning provisions were statistically associated (p<.05 or lower) with increased rates of walking, biking, or engaging in any active travel (walking, biking, or any active travel) to work: code reform zoning, bike parking (street furniture), bike lanes, bike-pedestrian trails/paths, other walkability, mixed use zoning, and a higher score on the zoning scale. Public transit use was associated with code reform zoning and a number of zoning measures in Southern jurisdictions but not in non-Southern jurisdictions. Conclusion: As jurisdictions revisit their zoning and land use policies, they may want to evaluate the pedestrian-orientation of their zoning codes so that they can plan for pedestrian improvements that will help to encourage active travel to work.